DEVELOPING A MODEL OF PLAY LEARNING IN CHARACTER-BASED SPORTS, HEALTH, AND PHYSICAL EDUCATION IN PRIMARY SCHOOL - Waluyo, Waluyo; Hidayatullah, Furqon; Kristiyanto, Agus (The Journal of Educational Development, 2017)
The goals to be achieved through this research is to result in a product in the form of a model of learning to play in the Health, Sports, and Physical Education (PJOK) in Primary School (SD). This learning model is expected to motivate and appeal learners to learn PJOK which in turn can be a means of internalizing the character values for learners. This study uses research and development approach developed by Borg and Gall. In this research and development design, there were 10 steps that should be implemented. For the benefit of this study, the researcher simplified the ten steps of research and development from Borg and Gall into three stages, namely (1) preliminary study, (2) model development, and (3) assessing the effectiveness of the model. As for the learning design model, this study refers to Dick, Carey, and Carey (2009). The trial employed a small group of students of SDN 15 and SDN 16 Laweyan.  The full trial employed a large number of learners of SDN 15 Laweyan, SDN 16 Laweyan, SD N Sumber I and SD N Sumber II. The test of the effectiveness was conducted in SDN 15 Laweyan attended by 32 students and the final product was disseminated in an international seminar. Instruments for gathering data were questionnaire and observation guidelines. Simple quantitative descriptive analysis techniques were employed to analyze the data. The results obtained in this research and development is an increase of scores from the first effectiveness test to the second one. The results of this research and development leads to some conclusions as follows: (1) The model of learning to play is capable of improving character values of hard work, discipline, tolerance, caring, creativity, honesty, friendship, responsibility; (2) The model learning to play is very effective as efforts to internalize the character values of hard work, discipline, tolerance, caring, creativity, honesty, friendship, and responsibility in learning Health, Sports, and Physical Education (PJOK)  that is based on character education in primary schools.